Комп'ютерне моделювання перерозподілу азоту в технологіях комплексного іонного азотування легованих сталей - Шевченко, Світлана Михайлівна; Терлецький, Олександр Семенович; Горова, Олена Павлівна; Соболь, Олег Валентинович; Протасенко, Тетяна Олександрівна; Реброва, Олена Михайлівна (Харківський національний автомобільно-дорожній університет, 2020)
Робота присвячена моделюванню за допомогою COMSOL Multiphysics 5.5 перерозподілу азоту в деталях з легованої сталі 9ХС у процесі їхнього ізотермічного відпалу або витримування під гартування після операції іонного азотування. Така технологія комплексного іонного азотування також передбачає низький відпуск після гартування та фінішну механічну обробку поверхні й має низку переваг порівняно з традиційними способами азотування. Для комплексного іонного азотування дуже актуальні оцінка і прогноз глибини проникнення азоту, тому моделювання проводили з метою дослідження дифузійного перерозподілу азоту в циліндричних пуансонах зі сталі 9ХС за умови температури 860 °С, які мали на поверхні готовий азотований шар завтовшки 80 мкм. Показано, що в зоні різальної кромки (окружності торця) пуансона спостерігається ефект підвищеного вмісту азоту в процесі його перерозподілу. Встановлено, що за прийнятих припущень перетворення ε-нітриду в азотистий аустеніт відбувається за 3,25 хв. Отримані концентраційні профілі перерозподілу азоту за умови різного часу витримування, які можуть застосовуватися для прогнозування в заводській практиці.

The work is devoted to modeling the redistribution of nitrogen in the parts made from alloy steel 9CrSi during isothermal annealing or holding for quenching after the operation of ionic nitriding. This integrated technology has a number of advantages over traditional nitriding methods. It is clear that assessment and prediction of the depth of nitrogen penetration are relevant for complex ion nitriding. Goal. Therefore, the purpose of the simulation was to study the diffusion redistribution of nitrogen in cylindrical punches made of 9CrSi steel at a temperature of 860 ° C, which had a finished nitrided layer with a thickness of 80 μm on the surface. Methodology. Externally, at a depth of up to 30 μm, the layer contained nitrides with a nitrogen concentration of 8.7% by mass, and deeper, up to 50 μm, - nitrogenous α-ferrite. Simulation was carried out in the COMSOL Multiphysics 5.5 software environment in the convection-diffusion module of classical differential equations. We used modern data on the diffusion coefficients in alloyed austenite and ε-nitride of steel. Within the framework of the initial conditions, for nitrogen, which forms solid solutions of interstitiality with carbon in phases, the mass percentages were recalculated into atomic ones with respect to the solid solution of substitution. The simulation results were programmatically returned to the usual atomic percentages. Results. In 3D modeling for up to 10 minutes, nitrogen redistribution from the end and a cylindrical 2 mm diameter of the lateral surface into the punch was assessed. It has been established that in the area of the cutting edge (end circumference) of the punch there is a geometric effect of increased nitrogen content during its redistribution. With a short holding time for hardening, this is an undesirable effect that must be taken into account by finishing machining. A more detailed simulation of the diffusion of nitrogen from the cylindrical surface of the punch into depth, taking into account the gradual transformation of the ε-nitride of the surface layer into austenite, was carried out in the 2D-simulation mode on the cross section. For this, the nitride layer was divided into ten sublayers, each 3 μm thick. The dependences of the nitrogen concentration in depth were obtained for different times of high-temperature holding up to 1 hour. Originality. Analysis of the data indicates that the nitride layer, despite its gradual dissolution in 3.25 min., decreases the average value of the concentration profile of nitrogen in austenite compared to the same initial conditions, but without nitrides. However, in this case, the depth of diffusion saturation, which gives a noticeable increase in microhardness, does not significantly decrease. Practical value. The simulation results correlate well with the microhardness data over the cross section of punches after complex ion nitriding and can be used for prediction in factory practice.
Computer modeling of nitrogen redistribution in technologies of complex ion nitriding of alloy steels
Keywords: хімічні технології; дифузія азоту; легований аустеніт; ε-нітрид; α-ферит; complex ion nitriding; steel 9CrSi; modeling; diffusion of nitrogen; alloyed austenite; ε-nitride; α-ferrite